Assessing clinical reasoning abilities of medical students using clinical performance examination - Im, Sunju (Korean J Med Educ, 2016)
PURPOSE: The purpose of this study is to investigate the reliability and validity of new clinical performance examination (CPX) for assessing clinical reasoning skills and evaluating clinical reasoning ability of the students. METHODS: Third-year medical school students (n=313) in Busan-Gyeongnam consortium in 2014 were included in the study. One of 12 stations was developed to assess clinical reasoning abilities. The scenario and checklists of the station were revised by six experts. Chief complaint of the case was rhinorrhea, accompanied by fever, headache, and vomiting. Checklists focused on identifying of the main problem and systematic approach to the problem. Students interviewed the patient and recorded subjective and objective findings, assessments, plans (SOAP) note for 15 minutes. Two professors assessed students simultaneously. We performed statistical analysis on their scores and survey. RESULTS: The Cronbach α of subject station was 0.878 and Cohen κ coefficient between graders was 0.785. Students agreed on CPX as an adequate tool to evaluate students’ performance, but some graders argued that the CPX failed to secure its validity due to their lack of understanding the case. One hundred eight students (34.5%) identified essential problem early and only 58 (18.5%) performed systematic history taking and physical examination. One hundred seventy-three of them (55.3%) communicated correct diagnosis with the patient. Most of them had trouble in writing SOAP notes. CONCLUSION: To gain reliability and validity, interrater agreement should be secured. Students' clinical reasoning skills were not enough. Students need to be trained on problem identification, reasoning skills and accurate record-keeping.